2007
DOI: 10.1021/jp0679257
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)-Bpy Complexes Bound to Nanocrystalline TiO2 Films through Phenyleneethynylene (OPE) Linkers:  Effect of the Linkers Length on Electron Injection Rates

Abstract: Three rigid-rod Ru-bpy sensitizers with linkers made of an oligo(phenyleneethynylene) (OPE) bridge varying in length (9.6-23.3 Å) and ending with an isophthalic acid anchroing unit were bound to TiO 2 (anatase) nanoparticle films, and the photoinduced electron injection rates for all three compounds were studied by femtosecond laser spectroscopy. The sensitized films were excited at 530 nm, in the MLCT region, and the injection dynamics was probed in the 600-1000 nm range. The excited state for all three compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…This synthetic pathway provides an effective monodentate anchoring group and increases the distance of the corrole macrocycle from the metal surface. It has been already proven that the length of the linker results in slower injection rates and that the presence of a cyanoacrylic acid moiety enhances the substrate absorption into thin films if compared with the only carboxylic acid counterpart …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This synthetic pathway provides an effective monodentate anchoring group and increases the distance of the corrole macrocycle from the metal surface. It has been already proven that the length of the linker results in slower injection rates and that the presence of a cyanoacrylic acid moiety enhances the substrate absorption into thin films if compared with the only carboxylic acid counterpart …”
Section: Introductionmentioning
confidence: 99%
“…It has been already proven that the length of the linker results in slower injection rates and that the presence of a cyanoacrylic acid moiety enhances the substrate absorption into thin films if compared with the only carboxylic acid counterpart. [23][24][25] To test the effectiveness of the binding event, two different corrole-coated ZnO nanoparticles were prepared. The hybrid materials were achieved with a one-pot technique, where the corrole was directly added to the precursor solution for the hydrothermal growth of ZnO nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published article on hole injection dynamics of ruthenium polypyridyl complexes into NiO, it was suggested, that the -I effect of the carboxylic anchoring groups (without linkers between chromophore and NiO) might hinder hole injection. [26,27] They suggest that direct contacts of the Ru complex in the sponge-like environment of the mesoporous TiO 2 films may act as "short-circuits", highlighting the importance of anchoring group design. [20] It is noteworthy that phosphonic esters can also be used to modify TiO 2 or other inorganic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning charge carrier transport there was only weak linker-length dependency. [26,27] They suggest that direct contacts of the Ru complex in the sponge-like environment of the mesoporous TiO 2 films may act as "short-circuits", highlighting the importance of anchoring group design. However, structure-property relationship studies for Ru-[(N ∧ N) 2 (C ∧ N)]+ derivatives, where N ∧ N represents 2,2Ј-bipyridine, and C ∧ N represents bidentate phenylpyridine derivatives with carboxylate anchoring groups, were performed by Wu et al for their application on NiO in p-type DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] A detailed understanding of the elementary processes on the surfaces, and their photoinduced dynamics requires a rational molecular design of model compounds. [5][6][7] It has been demonstrated that many properties of molecular adsorbate systems already depend upon the surface-immobilization strategy. [4,8] For example, the formation of aggregates strongly depends upon the orientation of single dye molecules and their lateral interaction on the metal or semiconductor surface.…”
Section: Introductionmentioning
confidence: 99%